Two new free-living nematode species (Comesomatidae) from the continental slope of New Zealand, with keys and notes on distribution - D., Leduc; K., Probert P.; D., Nodder S. (Zootaxa, 2012)
Two new free-living marine nematode species of the family Comesomatidae are described from the continental slope of NewZealand, and their distributions at 32 sites are investigated in relation to environmental factors. Vasostoma aurata n. sp. is char-acterised by a distinctly set-off head, amphideal fovea with 4.5 turns, conspicuous chords consisting of two bands fusing atbody extremities, with outline of cell bodies usually golden-coloured, and relatively short spicules. Setosabatieria conicauda n.sp. is characterised by an amphid with 4.25–4.5 turns, the presence of only 1–3 sub-cephalic setae per file, several clusters ofintracellular inclusions, sometimes brown-coloured, in the intestinal wall, and a conical tail. Keys to all known species of Seto-sabatieria and Vasostoma are provided. Both species were mostly restricted to subsurface (1–5cm depth) sediments. The abun-dance of V. aurata n. sp. and S. conicauda n. sp. was significantly correlated with food quantity and quality, but the patternsdiffered between species. The effect of food-related factors may be directly linked to interspecific differences in food require-ments, or mediated by biogeochemical processes (i.e., tolerance of sub-surface oxygen and sulphide concentrations). No signif-icant correlations were found between sediment granulometry and abundances, despite the wide range of sediment grain-sizes (6–93% silt and clay) at the sampling sites.